The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s13049-019-0602-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nitric oxide might be a contributing tool for successful resuscitation of cardiac arrest related to pulmonary hypertension

Abstract: We describe a case where inhaled nitric oxide (iNO) was successfully initiated during cardiopulmonary resuscitation (CPR) in a younger patient with cardiac arrest related to pulmonary hypertension after disseminated intravascular coagulation (DIC) postpartum bleeding and hysterectomy. This case illustrates that iNO might be a potential lifesaving tool for resuscitation of patients with cardiac arrest related to pulmonary hypertension, for whom most other resuscitation strategies often are futile. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Expected side effects such as systemic hypotension, bradycardia, pulmonary hypotension, kidney failure and methaemoglobinaemia, and platelet will be monitored and recorded as secondary endpoints. The dosage of 20 ppm is in accordance with previous trials, case reports and clinical experience and found to be an adequate balance between sufficient effect and potential side effects [6,7,[10][11][12]14].…”
Section: Plos Onesupporting
confidence: 65%
See 1 more Smart Citation
“…Expected side effects such as systemic hypotension, bradycardia, pulmonary hypotension, kidney failure and methaemoglobinaemia, and platelet will be monitored and recorded as secondary endpoints. The dosage of 20 ppm is in accordance with previous trials, case reports and clinical experience and found to be an adequate balance between sufficient effect and potential side effects [6,7,[10][11][12]14].…”
Section: Plos Onesupporting
confidence: 65%
“…A recent systematic review concludes that there is currently insufficient evidence to support long-term iNO in hypoxic respiratory failure [6]. Nevertheless, iNO used as a temporary measure on certain indications is widespread in adult critical care [7,[9][10][11]. During the current epidemic, iNO with doses starting at 20 parts per million (ppm) has successfully been used as rescue therapy to increase arterial oxygenation in patients with severe Covid-19 related ARDS [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…PAH is a serious, incurable cardiovascular disease with high mortality rate. There are several signaling pathways involved in regulation of hemodynamic changes using for therapeutic intervention in this clinical situation: prostaglandin one, with prostacyclin as a modeling substance, endothelin receptors, nitric oxide and cGMP pathway (with PDE type V inhibitors to increase intracellular concentration of this second messenger) [9][10][11].…”
Section: Discussionmentioning
confidence: 99%